Catalisadores de Co e Pt suportados em La2O3 e SiO2 aplicados na reforma a vapor do etanol - Baldoino, Marília Gabriela Branquinho (Universidade Federal de São Carlos, 2015)
In intense search best environmental conditions, it is necessary to invest in renewable fuels, affordable and low polluting. With the aim to participate in this effort, this work was undertaken to study the steam reforming of ethanol. Cobalt catalysts supported on SiO2 were studied using mass loading of lanthanum 10, 20 and 30% mass content, and 0,5% platinum as additives in order to check their influences on the initial catalyst to reduce carbon formation on the catalyst surface, enhancing the activity, stability and selectivity for H2. All catalysts were prepared by impregnation method. Were characterized by temperature programmed reduction in H2, Hydrogen Chemisorption, surface area by BET, X ray diffraction method, thermo gravimetric analysis and chemical analysis. Subsequently, the reaction RVE catalysts, which was analyzed in conversion and selectivity were applied. The TPR and XRD analyzes observed the formation of Co3O4 which espinélia phase is reduced to CoO and Co°, respectively. Subsequently, the catalysts were used for ethanol steam reforming reaction, where the conversion, selectivity, and stability was analyzed. In XRD analysis and RTP observed the formation of Co3O4 that espinélia phase and reduces CoO and Co°, respectively. Also, it was identified diffraction peaks relating to La2O3 and La(OH)3; platinum, and a broad peak was assigned to the SiO2 structure, which has low crystallinity. There was a decrease in coking catalysts, effect obtained by forming lanthanum oxicarbonate, which was also identified by XRD. The increased lanthanum loading also influence the decrease in particle size, thereby increasing the dispersion of the catalysts. During the 24-hour stability test, the catalyst is not desactivated. It was identified that the impregnation method used and the utilized treating conditions were adequate to obtain the desired compounds for reform to ethanol vapor. The CoLa2SiO2 catalyst showed promise for ethanol steam reforming, with better selectivity to hydrogen, with little formation of undesirable products. The addition of 0.5% by mass Pt content in the cobalt catalyst has not led to a significant increase in product formation and conversion. The monometallic Pt catalyst (0.5% w / w) proved active and with good hydrogen selectivity even with a small amount of active phase. This behavior can be related to the presence of highly dispersed platinum metal on the surface. The best performing catalysts did not show the formation of CO, which can be related to the addition of lanthanum.
Keywords: Etanol; Reforma a vapor; Hidrogênio; Catalisadores; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA